Defining exacerbations in chronic obstructive pulmonary disease. (June 2015) - Hawkins, Padraig E; Alam, Jamshed; McDonnell, Timothy J; Kelly, Emer
Abstract : Chronic obstructive pulmonary disease is a very common disease often punctuated by intermittent episodes of exacerbation. These exacerbations affect the natural history of the disease, accelerating a decline in lung function. They affect the individual in many ways and affect the health service caring for these patients. The definition of exacerbation varies and lacks clarity. The definitions used most are either symptom based, for example, breathlessness, sputum production and sputum purulence, or event driven, for example, an event causing a patient to seek healthcare input or change to medications. In this article, we discuss the importance of exacerbations, the clinical definitions, clinical trial definitions, physiological and biomarker evidence of exacerbations and the challenges associated with each of these. Application of a practical definition would aid in our clinical management of patients with chronic obstructive pulmonary disease and facilitate developments in future therapeutic advances through clinical trials.